The Role of Chelators in Surface Metabolism of Adenosine Nucleotides Added to Native Human Blood Platelets in Vitro - Kerby, G. P (Thrombosis and Haemostasis, 1966)
The production of ATP and AMP by human platelets exposed in this study to a large excess of exogenous ADP has been confirmed, using nonanticoagulated platelet-rich-plasma. Production of ATP differed from that of AMP in that divalent cation requirements were not the same, and there were differences in sources yielding maximal production. ATP production proceeded in the absence of free calcium ions, although it was enhanced by their presence. AMP production was partially or completely arrested by full EDTA chelation of the same platelet mixture. Citrate anion regularly enhanced the net production of AMP (but not of ATP) when added to native platelet-rich-plasma, provided some free calcium ions were present. When native human platelets were resuspended in serum from autologous platelet-poor-plasma, ATP production was markedly greater with unwashed platelets than with washed (glucose-phosphate buffer) platelets, while the reverse was true of net AMP production. An important initial role by adenylate kinase is therefore unlikely in this in vitro system. The net production of both ATP and AMP was much greater in serum derived from non-anticoagulated platelet-rich-plasma and from whole blood than from serum derived from non-anticoagulant platelet-poor-plasma, again emphasizing the importance of platelet enzymes, among others, in the overall reactions observed.